1975
DOI: 10.1159/000127789
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute Ischemia on the Motility of the Small Bowel in the Awake Dog

Abstract: The effect of acute ischemia obtained by clamping the feeding arteries was studied on a 30-cm loop of upper jejunum in mongrel dogs. In order to eliminate the side-effects of anesthetics on the small bowel, the studies were performed on the awake dog, where access to the upper jejunum was permitted by the construction of a jejunostomy with a Roux-en-Y anastomosis for reestablishment of intestinal continuity. The motility was estimated after stimulation of the mucosa with a standard bolus of isotonic 0.1 NHC1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

1986
1986
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
0
4
0
4
Order By: Relevance
“…This phenomenon of adynamic ileus that can be seen after abdominal surgery is dependent on the duration of ischemia and/or reperfusion. Studies in awake dogs showed that short ischemia caused immediate hyperexcitability of the segment of small bowel, however longer duration of ischemic injury caused delay in gastric emptying and slowing of the small intestinal motility [2][3][4][5][6]. The results of the present study demonstrate that sham operation leads to inhibition of bowel motility, which is exacerbated by ischemia-reperfusion and that this inhibition is abolished by ET-receptor antagonist in the late reperfusion period.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This phenomenon of adynamic ileus that can be seen after abdominal surgery is dependent on the duration of ischemia and/or reperfusion. Studies in awake dogs showed that short ischemia caused immediate hyperexcitability of the segment of small bowel, however longer duration of ischemic injury caused delay in gastric emptying and slowing of the small intestinal motility [2][3][4][5][6]. The results of the present study demonstrate that sham operation leads to inhibition of bowel motility, which is exacerbated by ischemia-reperfusion and that this inhibition is abolished by ET-receptor antagonist in the late reperfusion period.…”
Section: Discussionmentioning
confidence: 55%
“…Ischemic lesions of the small bowel may be the result of a variety of clinical conditions associated with a decrease or redistribution of blood flow, such as shock, congestive heart failure, mesenteric embolus, small bowel obstruction, cardiopulmonary by pass and hypothermia. It was shown that brief periods of acute intestinal ischemia cause immediate hyperexcitability [2][3][4], longer periods of ischemia cause prolonged inhibition of bowel motility [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…A eletromiografia determina a viabilidade intestinal através da avaliação da atividade das ondas lentas na parede do intestino. O estado isquêmico gera alterações previsíveis nos padrões de atividade dessas ondas lentas, sendo que a sua freqüência diminue progressivamente com o aumento do tempo de isquemia quente 34,44 . Um estudo recente de Lammers et al 47 mostrou em gatos que na isquemia mesentérica aguda há uma diminuição progressiva e não-homogênea na condução das ondas lentas e na excitabilidade local da parede intestinal.…”
Section: Eletromiografia Intestinalunclassified
“…Όταν ο χρόνος της "θερμής" ισχαιμίας ήταν μεγαλύτερος από 4 ώρες, τα γαγγλιονικά κύτταρα και οι λείες μυϊκές ίνες καταστρέφονταν. Έτσι, η ικανότητα του εντέρου να εμφανίζει δυνα μικά αιχμής, μετά ηλεκτρική ή χημική διέγερση, μειωνόταν 21,22 . Οι Cabot και Kohatsu (1978) 23 όμως, απέδειξαν ότι σε χρόνο "θερμής" ισχαιμίας 18 ωρών δεν επερχόταν πλήρης εξάλλειψη της συσταλτικής ικανότητας των λείων μυών.…”
Section: ι±κολικ:ίί_ισχαιμίαunclassified
“…Έτσι απαιτούνταν προο δευτική αύξηση του ελάχιστου ρεύματος διέγερσης,για να προκληθεί σύ σπαση του εντέρου,από τα 12mAmp περίπου για το φυσιολογικό παχύ έντερο μέχρι την μέγιστη τιμή των lOOmAmp καθώς μεγάλωνε η ισχαιμία προς το κεντρικό, νεκρωμένο τμήμα της έλικας (σχ. 17,19,20,21). Το νε κρωμένο τμήμα συνήθως δεν συσπώταν καθόλου.…”
Section: Ulmexphzelzjltojzxalmiko_nax>l£mt_eeqrzyrkeizh ιων_μεθ_οδωνunclassified